If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 3x + -9 Reorder the terms: 5y = -9 + 3x Solving 5y = -9 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = -1.8 + 0.6x Simplifying y = -1.8 + 0.6x
| 7(7b+2)=-378 | | 5x-21=x+15 | | 84=6(6+m) | | -x+14y=15 | | 12y=-10x-60 | | -9x+l=-80 | | 2(3x-6)=6(x-6) | | 3x-8=2x-15 | | f(x)=(x+6)2+14 | | 5(x+23)= | | 62*26=x | | -.33(9x+18)= | | 6.3=-8+x | | 2x+5x-8=6 | | 5.7=-9+x | | 6x+5x-9=35 | | x^2+33x= | | x^2+33= | | 8d+9=4d+45 | | -5=x.4 | | x^2+24x= | | 4(x-9)=-21.6 | | 3/4(x+1)=20 | | 2(a+7)=29.4 | | -1.4=3c-8 | | -5.9+y=-4.7 | | xsquared+3x-9=0 | | 3y=6-9 | | (9x+8)(8x-9)= | | 6-n=-6-3n | | 3x+6-4x+12=12 | | 110=39.41+.25x |